Energy Level Alignment at Interfaces Between Au (111) and Thiolated Oligophenylenes of Increasing Chain Size: Theoretical Evidence of Pinning Effects. Issue 3 (13th February 2018) - Diez‐Cabanes, Valentin; Gonzalez, Sandra Rodriguez; Osella, Silvio; Cornil, David; Van Dyck, Colin; Cornil, Jérôme
Abstract: We present a detailed theoretical characterization of the energetic alignment between the HOMO level of a series of thiolated oligophenylenes of increasing chain size, and the Fermi level of gold electrodes, using density functional theory (DFT) calculations for molecular self‐assembled monolayers (SAMs) chemisorbed on an Au (111) surface, and the nonequilibrium Green's function (NEGF) formalism coupled to DFT for single molecule junctions. The additional role of the dynamic electronic polarization effects neglected in standard DFT calculations is also discussed. Interestingly, whereas the HOMO energy varies significantly among the unsubstituted oligomers in the gas phase, their alignment with respect to the Fermi level of the electrode is almost insensitive to chain size upon chemisorption, thus pointing to a strong pinning effect. The energy at which the HOMO is pinned strongly depends on the degree of interfacial hybridization, and hence on the contact geometry, as well as on the degree of surface coverage although a different mechanism enters into play. Abstract : Whereas the HOMO energy of isolated oligophenylenes of increasing size varies significantly, the DFT calculations shown here demonstrate that their alignment with respect to the Fermi level of gold is almost insensitive to chain size upon chemisorption, thus pointing to a pronounced pinning effect. The energy at which the HOMO is pinned strongly depends on the degree of interfacial hybridization and degree of surface coverage.